Analgesic Activity Test Of Leunca Leaves (Solanum nigrum L.) Ethanol Extract With Randall Selitto Method - Ariasti, Mia; Sofya, Sri Winarni (Jurnal Pijar Mipa, 2025)
Abstract: Pain is a sensory and emotional experience related to tissue damage. This study aims to determine the analgesic effect of leunca leaf ethanol extract and determine the dose of leunca leaf ethanol extract that has the highest analgesic activity with the Randall Selitto method. Randall Selitto method has been widely used for the development of non-steroidal anti-inflammatory drugs. Leunca leaf powder was extracted using maceration method with 96% ethanol solvent. A total of 25 wistar male white rats were divided into 5 groups, namely positive control mefenamic acid 9 mg / 200 g BW, negative control CMC Na 1%, ethanol extract of leunca leaves doses of 5 mg / 200 g BW, 10 mg / 200 g BW and 20 mg / 200 g BW. The data obtained were analyzed by ANOVA test, then LSD test was used to determine the differences between groups. The results showed that the extract doses of 5 mg / 200 g BW, 10 mg / 200 g BW, 20 mg / 200 g BW and positive control were significantly different from the negative control group. The extract dose of 20 mg / 200 g BB is comparable to the positive control, indicating that the extract dose of 20 mg / 200 g BB has the highest analgesic activity. Steroid and flavonoid compounds contained in leunca leaves are thought to have an effect as analgesics.